Development of ISBAR-Based Anesthesia Unit Handover Instrument with Android Apps Against Completeness Pre and Post Anesthesia Documentation in the Installation Central Surgery - Putra, Dony Dwi Purnama; Bakr, Abu; Hidayati, Laily (Indonesian Journal of Global Health Research, 2024)
The completeness of anesthesia records both electronically and handwritten is an important measure of information during perioperatives, as well as a legal document against anesthesia providers.The development of a handover instrument model with an android application with Kopelman model theory is needed in order to create an effective handover in the policy of supporting infrastructure and the implementation of anesthesia as an evaluation of the completeness of anesthesia documentation. This study aims to develop an ISBAR instrument with an android application as a guide for the handover of the anesthesia unit at the Central Surgical Installation of RSUD Haji Surabaya. Method: Research design using Research and Development (R&D). The independent variable is the development of ISBAR-based handover instruments, and the dependent variable taken is the completeness of pre- and post-anesthesia documentation. The population was taken as many as 34 nurse anesthetists and 100 pre and post anesthesia documentation, sampling using purposive sampling. The instruments used are questionnaires and observation sheetsResults: The trial of the anesthesia handover using the ISBAR instrument on the android application using the SUS questionnaire obtained 85 results meaning acceptable. Analysis: In stage 1 using descriptive analysis to determine the frequency of data, while in stage 2 using descriptive analysis presented in percentage to show the presentation of application test feasibility results. Conclusions: The development of ISBAR handover instruments with andorrid applications is suitable for use during operational services with Acceptability Ranges conditions that are acceptable. Grade Scale includes B. Adjective Rating: Worst Imaginable results are Excellent and Percentiles results are good.